Screening of Germplasm Against Alternaria Leaf Spot in Niger (Guizotia abbyssinica (L.f.) Cass) - Suvarna; A. S., Savitha; R, Lokesha (International Journal of Bio-resource and Stress Management, 2020)
Niger (Guizotia abbyssinica (L.f.) cass) is a minor oilseed crop in India, cultivated on a marginal and sub-marginal lands, hilly areas, sloppy areas and around forest lands. It has tolerance to insect pests, diseases and attack of wild animals. In order to evaluate niger germplasm for Alternaria leaf spot disease, 200 lines were collected from Project Coordinating Unit, Jabalpur and were screened for disease resistance during kharif 2013 at College of Agriculture, UAS, Raichur. Each germplasm line was sown in a single line. The same were evaluated for seed yield and other ancillary characteristics viz., days to 50% flowering, days to maturity, plant height, number of primary branches, number of capitula and seed yield. Among 200 lines sown, 189 lines were germinated and evaluated for disease incidence during flowering time. The 0-5 scale was used to score the disease. 32 lines were found to be immune as these didn’t showed any infection (i.e. 0% infection). The 100 lines were scored 1 by showing 1-10% disease incidence and are found to be resistant. The remaining germplasm (57) lines were scored 2 by showing 11-25% disease incidence and are moderately resistant. None of the genotypes were found to be susceptible. For confirmation, the disease scoring is in progress under epiphytotic condition. The genotypes with high yielding and less/no disease incidence were also identified. So collecting and evaluating germplasm for disease incidence will help in boosting the process of development of high yielding disease resistant varieties of niger.